2016
DOI: 10.1103/physrevb.93.085205
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced tunability of the reststrahlen band in4HSiC

Abstract: Materials with a negative dielectric permittivity (e.g. metals) display high reflectance and can be shaped into nanoscale optical-resonators exhibiting extreme mode confinement, a central theme of nanophotonics. However, the ability to actively tune these effects remains elusive. By photoexciting free carriers in 4H-SiC, we induce dramatic changes in reflectance near the "Reststrahlen band" where the permittivity is negative due to charge oscillations of the polar optical phonons in the mid-infrared. We infer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 29 publications
(89 reference statements)
0
38
0
Order By: Relevance
“…However, advances in nanophotonics have produced ultrathin, so-called "flat" optical components that beget abrupt changes in these properties over distances significantly shorter than the free space wavelength. [1][2][3][4][5][6][7][8] While high optical losses still plague many approaches, 9 phonon polariton (PhP) materials have demonstrated long lifetimes for sub-diffractional modes [10][11][12][13] in comparison to plasmon-polariton-based nanophotonics. We experimentally observe a three-fold improvement in polariton lifetime through isotopic enrichment of hexagonal boron nitride (hBN).…”
mentioning
confidence: 99%
“…However, advances in nanophotonics have produced ultrathin, so-called "flat" optical components that beget abrupt changes in these properties over distances significantly shorter than the free space wavelength. [1][2][3][4][5][6][7][8] While high optical losses still plague many approaches, 9 phonon polariton (PhP) materials have demonstrated long lifetimes for sub-diffractional modes [10][11][12][13] in comparison to plasmon-polariton-based nanophotonics. We experimentally observe a three-fold improvement in polariton lifetime through isotopic enrichment of hexagonal boron nitride (hBN).…”
mentioning
confidence: 99%
“…Off the array, the response is negative, indicating a lower reflectivity consistent with Reststrahlen-band softening. 37 For both nanostructure resonances and bulk SiC, a portion of the response was observed to recover exponentially in ~ 140 ps, after which the remainder of the signal persists for > 500 ps. Prior work has shown that the bulk carrier recombination lifetime is dominated by Shockley-Read-Hall processes with a lifetime of 900 ns.…”
Section: Active Tuning In Inp Nanopillarsmentioning
confidence: 96%
“…The magnitude of the resonance shifts and the associated broadening of the SPhP resonances with increasing photoinjected carrier density are qualitatively reproduced by finitedifference time-domain (FDTD) simulations (Fig 3c). For the calculated spectra, the 4H-SiC dielectric function was taken from Spann et al 37 with the free-carrier damping time fixed at 12.5 fs. The experimental and calculated spectral shifts of the transverse dipole resonance with carrier concentration are provided in Fig.…”
Section: Active Tuning In Inp Nanopillarsmentioning
confidence: 99%
“…A promising alternative in the midinfrared is surface phonon polariton (SPhP) light concentrators, which permit deep subwavelength light confinement by storing electromagnetic energy as vibrations of the crystal lattice [5][6][7]. Localization of SPhPs in user-defined resonators [8] allows for extremely small mode volumes [9,10] in highly tunable low-loss modes [11][12][13][14], with applications in sensing [15], nonlinear optics [16,17], and the creation of nanophotonic circuitry [18][19][20].…”
Section: Introductionmentioning
confidence: 99%